Исследование избыточного давления вскрытия заполнений проемов вертикальных строительных конструкций - Usov А.; Penyaz’kov О.Г.; Mikanovich Андрей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
Within last two years in Byelorussia in quality easy-dropped constructions application double-glazing units which behaviour at deflagration explosion is not investigated is supposed. For carrying out of researches the test facility for definition of superfluous pressure of opening of window blocks is developed at deflagration explosion in the closed volume.